2014
DOI: 10.3892/etm.2014.1927
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of mismatch repair gene expression in sporadic colorectal cancer

Abstract: Mismatch repair (MMR) genes play an important role in the occurrence and development of sporadic colorectal cancer; however, the effect of MMR genes on clinicopathological features and prognosis remains unclear. The aim of the present study was to observe the clinical significance of MMR gene expression in sporadic colorectal cancer. Clinicopathological data and postoperative samples from 404 patients with sporadic colorectal cancer were obtained from the Affiliated Tumor Hospital of Xinjiang Medical Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…As is well established in the literature, MSI-H CRCs are also associated with poor differentiation [19,37], are larger and more likely to be mucinous [38][39][40], as well as being higher grade tumours with a greater mutational burden and the mucinous phenotype more likely to be associated with signet cells. It is also believed that MSI-H CRCs are associated with a high number of frameshift mutation peptides (FSPs) [41,42] when compared to MSS CRCs [43,44]. The MSI hyper-mutational state is also thought to be the reason for poor differentiation and other adverse pathological features of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…As is well established in the literature, MSI-H CRCs are also associated with poor differentiation [19,37], are larger and more likely to be mucinous [38][39][40], as well as being higher grade tumours with a greater mutational burden and the mucinous phenotype more likely to be associated with signet cells. It is also believed that MSI-H CRCs are associated with a high number of frameshift mutation peptides (FSPs) [41,42] when compared to MSS CRCs [43,44]. The MSI hyper-mutational state is also thought to be the reason for poor differentiation and other adverse pathological features of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yoon et al ( 11 ) evaluated 2,028 tumour samples, and found that MSI-high tumours were typically larger. However, both Sun et al ( 12 ) and Faghani et al ( 13 ) have reported that there was no significant relationship between tumour size and MMR status. Interestingly, the MMR system can activate cell-cycle checkpoints or apoptosis, which might partially explain the occurrence of over-proliferation in tumours with defective MMR.…”
Section: Discussionmentioning
confidence: 96%
“… 11 - 13 , 24 , 26 Four studies showed longer DFS in the patients with CRC with deficient hMLH1 or hMSH2. 14 - 16 , 28 However, Bendardaf et al suggested that deficient MMR demonstrated a shorter DFS. This inconsistency could be explained by combining with other genes (TS) and distinctive clinic features indicating that CRC with deficient MMR is apt to display marked peritumoral and intratumoral lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 99%